DURABILITY OF BIOLOGICAL PROSTHESES USED FOR MANAGEMENT OF DEGENERATIVE AORTIC STENOSIS - TAVR vs. SAVR - Veselin Valkov; Dobrin Kalchev; Atanas Kostadino; Yavor Kashlov; Branimir Kanazirev (Peytchinski Publishing, 2018)
The only known treatment for high grade degenerative aortic stenosis until the beginning of this century was surgical replacement with a biological or mechanical valve. For the high risk or inoperable patients this treatment was unacceptable, with a high mortality rate in both operated and non-operated cases. The new concept of transcatheter valve implantation was developed especially for this group of patients, which number continues to increase. It is a really attractive idea, being able to offer a non-invasive and low risk procedure for a patient who is not considered a good candidate for conventional operation. The increase in the operators experience reduces the rate of mortality in TAVI even more. Both TAVI and surgical valves are biological. The technology used for production of the balloon expandable and self-expandable valves is much more advanced. The biological tissue used in both types of valve is prone to degeneration due to different factors and can lead to valvular dysfunction. The surgical valves are made from porcine or bovine tissue and have a lifespan between 10 and 15 years. In some cases, the dysfunction occurs much sooner. If that happens the patient needs a re-replacement valve surgery. Since such a procedure is risky the patient is usually referred for valve-in-valve TAVI.